2017
DOI: 10.1002/jcb.26474
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the CRISPR/Cas9 toolkit for Pichia pastoris with efficient donor integration and alternative resistance markers

Abstract: Komagataella phaffii (syn. Pichia pastoris) is one of the most commonly used host systems for recombinant protein expression. Achieving targeted genetic modifications had been hindered by low frequencies of homologous recombination (HR). Recently, a CRISPR/Cas9 genome editing system has been implemented for P. pastoris enabling gene knockouts based on indels (insertion, deletions) via non‐homologous end joining (NHEJ) at near 100% efficiency. However, specifically integrating homologous donor cassettes via HR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 56 publications
(121 reference statements)
1
94
1
Order By: Relevance
“…We envision our deletion plasmids to be used to generate knockout strains that can be mated and analysed by tetrad dissection. We further suggest to use our vectors in combination with a recently developed CRISPR/Cas9 approach (Weninger et al, ), which still requires the cloning of repair cassettes of several kbs. Genome editing of P. pastoris applying CRISPR/Cas9 is working much more efficiently in a ku70 Δ strain background than in wild type cells, which is why the use of efficiently working selection markers in the repair cassettes drastically facilitates identification of strains with correct genetic alterations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We envision our deletion plasmids to be used to generate knockout strains that can be mated and analysed by tetrad dissection. We further suggest to use our vectors in combination with a recently developed CRISPR/Cas9 approach (Weninger et al, ), which still requires the cloning of repair cassettes of several kbs. Genome editing of P. pastoris applying CRISPR/Cas9 is working much more efficiently in a ku70 Δ strain background than in wild type cells, which is why the use of efficiently working selection markers in the repair cassettes drastically facilitates identification of strains with correct genetic alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies were shown to improve HR activity in P. pastoris such as hydroxyurea‐mediated cell cycle arrest (Tsakraklides et al, ), increasing the genetic redundancy of host cells by providing extra copies of the gene to be deleted on a helper plasmid (Chen et al, ) or deletion of KU70 , a key player in NHEJ improved targeting (Näätsaari et al, ). Deletion of KU70 was also shown to drastically improved gene modifications using CRISPR/Cas9 tools (Weninger et al, ). However, disadvantages such as high complexity, low strain fitness, or not yet fully realized methods for donor cassette integration have kept these techniques from replacing the established ones for the efficient construction of producer strains.…”
Section: Introductionmentioning
confidence: 99%
“…Stadlmayr et al reported the screening of highly secreting strains by constructing cDNA overexpression libraries but only one gene per strain was perturbed in this strategy so that the coordination between genes could not be examined. Therefore, more efficient genome‐scale perturbation methods such as gTME (global transcription machinery engineering) , MAGE (multiplex automated genome engineering), GREASE (genome replication engineering‐assisted continuous evolution), and more recently CRISPR/Cas9 will pave the way for the modification of complex phenotypes such as secretion capability and cell robustness.…”
Section: Perspectivesmentioning
confidence: 99%
“…The discovery of the CRISPR‐Cas9 genome editing system has revolutionized synthetic biology by allowing fast genetic manipulation in a variety of applications. CRISPR‐Cas9 has been implemented in a variety of S. cerevisiae backgrounds, including strains used in the brewing and wine industries (Denby et al, ; Gorter de Vries, de Groot, van den Broek, & Daran, ; Vigentini, Gebbia, Belotti, Foschino, & Roth, ) and other industrially relevant yeast species such as fission yeasts (Jacobs, Ciccaglione, Tournier, & Zaratiegui, ), Kluyveromyces marxianus (Lee et al, ), Yarrowia lipolityca (Schwartz & Wheeldon, ; Shi, Huang, Kerkhoven, & Ji, ), Ogatae species (Juergens et al, ), and Pichia species (Weninger et al, ). Of particular relevance is the development of optimized CRISPR‐Cas9 methods to engineer diploid and polyploid industrial yeast strains (Stovicek, Borja, Forster, & Borodina, ; Zhang et al, ).…”
Section: Crispr For Rapid Multiplex Engineering Of Cell Factoriesmentioning
confidence: 99%